The Role of Music Education in Childhood - Szűcs Tímea; Juhász Erika (Sciendo, 2023)
Introduction: From the second half of the 20th century onwards, studies on the transfer effects of music learning have become increasingly common. Both in the domestic and international literature, we can read research with a solid scientific background that supports the transfer effects of music education on different aspects of life.